8 Preventing deaths and injuries from house fires: a cost benefit analysis of a community-based smoke alarm installation programme. (19th September 2017) - Yellman, Merissa; McCoy, Mary; Stephens-Stidham, Shelli; Caton, Emily; Barnard, Jeffrey; Padgett, Ted; Istre, Gregory
Abstract : Statement of purpose: This study was to estimate the cost-benefit of Operation Installation (OI), a community-based smoke alarm installation programme in Dallas, Texas. OI targets houses in high-risk urban census tracts. Residents of houses that received OI installation (or programme houses) had 68% fewer medically treated house fire injuries (non-fatal and fatal) compared with residents of non-programme houses over an average of 5.2 years of follow-up during an effectiveness evaluation conducted from 2001 to 2011. Methods/approach: A mathematical model incorporated programme cost and effectiveness data as directly observed in OI. The estimated cost per smoke alarm installed was based on a retrospective analysis of OI expenditures from administrative records, 2006–2011. Injury incidence assumptions for a population that had the OI programme compared with the same population without the OI programme was based on the previous OI effectiveness study, 2001–2011. Unit costs for medical care and lost productivity associated with fire injuries were from a national public database. Results: From a combined payers' perspective limited to direct programme and medical costs, the estimated incremental cost per fire injury averted through the OI installation programme was $1 28 800 (2013 US$). When a conservative estimate of lost productivity among victims was included, the incremental cost per fire injury averted was negative, suggesting long-term cost savings from the programme. The OI programme from 2001 to 2011 resulted in an estimated net savings of $3.8 million, or a $3.21 return on investment for every dollar spent on the programme using a societal cost perspective. Conclusions: Community smoke alarm installation programmes could be cost-beneficial in high-fire-risk neighbourhoods. Significance/contribution to Injury and Violence Prevention Science: To our knowledge, this is the only cost-benefit analysis of a 10 year smoke alarm installation program.